You are on page 1of 8

2004

. f ' x0
. f x0
, f(x0) = 0.
10

. f x0
;
5

.

.

.
.
2

. lim f(x) = l , lim f(x) = lim+ f(x) = l


x x 0 x x 0 x x 0
2

. f, g x0, fg
x0 :
(fg)(x0) = f'(x0) g(x0).
2

. f, .
f(x)>0 x , f
.
2

. f ' [, ]. G
f [, ],


f(t)dt = G() G()
2

: Keystone 1
2

f f(x)=x2 lnx.

. f,
.
10
. f
.
8
. f.
7

g(x)=exf(x), f R
3
f (0) = f = 0 .
2
3
. 0,
2
f()=-f().
8

. f(x)=2x2-3x,
0
I() = g(x)dx, R .

. lim () .

9

f: R R f(1)=1. x R,

x3 1
g(x) = z f (t) dt 3 z + (x 1) 0 ,
1 z
z=+i C, , R*, :

. g R
g.
5

1
. z = z + .
z
8

.
1
Re(z 2 ) = .
2
6

: Keystone 2
. f(2)=>0, f(3)= >, x0
(2, 3) f(x0)=0.
6

: Keystone 3

. (Fermat) . 260 . .

. . 213 . .

(*) 1
f
( a, x0 ) ( x0 , ) . ,
. lim f ( x ) = lim + f ( x ) = l lim f ( x ) = l ,
x x0 x x0 x x0


f ( a, x0 ) ( x0 , ) .
, .

. x>0. A f = (0,+ ) .
H f (0,+ )

f ' ( x ) = ( x 2 ln x ) ' = ( x 2 ) ' ln x + x 2 (ln x ) ' =


1
= 2 x ln x + x 2 = 2 x ln x + x = x (2 ln x + 1)
x

:
f ' (x) = 0 x (2 ln x + 1) = 0 . :
x=0 A f = (0,+ )
1
1
2 ln x + 1 = 0 ln x = x=e 2.
2

f :

: Keystone 4
1 1

(0, e 2
] , (0, e ] 2

1

f (x) <0 (0, e 2
).

1 1

[e 2
,+) , [e ,+) 2

1

f (x) >0 ( e 2
,+) .
1

x = e 2

1 1 1

2 2
1 1
f (e ) = ( e ) ln e
2 2
= e 1 =
2 2e

. f 2 (0,+)

f ' ' ( x ) = (2 x ln x + x ) ' = 2 ln x + 2 + 1 = 2 ln x + 3 .

:
3
3
f ' ' (x) = 0 2 ln x + 3 = 0 ln x = x=e 2
2

3 3 3
3 3
f ( e ) = ( e ) ln( e ) = e 3 = 3 .
2 2 2 2
2 2e

f :
3

(0, e 2
]
3

[e 2
,+ ) .
3
3
( e 2
, ).
2e3

. :
ln x ( De L ' Hospital )
lim+ f ( x ) = lim+ x 2 ln x = lim+ =
xo xo x o 1
x2
1
x x4 x2
= lim+ = lim = lim+ =0.
xo 2 x x o + 2 x 2 x o 2
4
x

: Keystone 5

x + x +
(
lim f ( x ) = lim x 2 ln x = + . )
1

f (0, e 2
] ,

1
1
f (0, e ] = [ ,0) .
2

2e

1

f [e 2
,+ )

1
1
f [e ,+) = [ ,+) .
2

2e

1 1 1
f f ((0,+) ) = [ ,0) [ ,+ ) = [ ,+ ) .
2e 2e 2e
, ,
.

. f R, g R
. g
R.
3 3
g 0, R 0, R
2 2
g' (x) = e x f(x) + e x f ' (x) .
g(0) = e0 f(0) = 0
3 3
3 2
3 g(0) = g .
g = e f = 0 2
2 2
3
Rolle 0,
2
J =  H I + H I =  H (I ) + I  =  .
3
e 0 0,
2
f() = -f().

. f(x) = 2x2 - 3x

g(x)dx = e (2x ) ( )( )
0 0 0
()=
x 2
3x dx = e x 2x 2 3x dx =

[ ]
= e x (2x 2 3x ) e x (2x 2 3x) ' dx =
0 0

[ ]
0 0


[ ]
= e x (2x 2 3x ) e x (4x 3)dx = e x (2x 2 3x ) (e x ) (4x 3)dx =
0 0

[ ] [
0
]
= e x (2x 2 3x ) e x (4x 3) + e x (4x 3) ' dx =
0 0

: Keystone 6
[ (
= e x 2x 2 3x )] [e (4x 3)] +
0

x 0


0
e x 4dx =

[ (
= e x 2x 2 3x )] [e (4x 3)]
0

x 0
+ 4 ex [ ]
0
=

( )
= e 2 2 3 e 0 (3) + e (4 3) + 4e 0 4e =

( )
= e 2 2 3 + 3 + e (4 3) + 4 4e = 7 + e 4 - 3 - 2 2 + 3 4 = ( )
(
= 7 + e - 2 2 + 7 7 . )

( 2
() = 7 + e - 2 + 7 7 , R . )
2 7 7
. < 0 , () = 7 + e a 2 + 2 .
a a
+ +
2 + 2 2

2
(
lim e = lim
1
)
= lim
e
= lim = 0
e

e
7 7
lim 2 + 2 = 2


lim () = 7 + 0(2) = 7 .

. g(x) :
x3
1
g ( x ) = z f (t )dt 3 z + ( x 1) .
1
z
x
f R, (x)= f (t )dt
1

.
3
, h( x ) = x R .
x3
F ( x ) = f (t )dt = (h (x )) R
1
h R,
F ' ( x ) = f ( x 3 ) 3x 2 = 3x 2 f ( x 3 ) .
1
l ( x ) = 3 z + ( x 1) R
z
1
l' ( x ) = 3 z + .
z
g R

1
g ' ( x ) = 3x 2 z f ( x 3 ) 3 z + .
z

: Keystone 7
. g ( x ) 0 x R g(1)=0, :
g ( x ) g (1) x R .
g x0=1
. Fermat g(1)=0.

1
g(1)= 3 z f (1) 3 z + f(1)=1
z
1
g(1)= 3 z 3 z + .
z
1
g(1)=0, z = z + .
z

2
1 2 1 1 1
. z = z + , z = z + z z = ( z + ) (z + )
z z z z
z z 1
zz = zz + + + 0 = z 2 + z 2 + 1 z 2 + z 2 = 1
z z zz
_
1
z 2 + z 2 = 1 2 Re( z 2 ) = 1 Re( z 2 ) = .
2

.
z 2 = ( a + i ) 2 = 2 2 + 2 i Re( z 2 ) = a 2 2
:
1 1
a 2 2 = ( ) ( + ) = .
2 2
>

+ < 0 , < < 0 .

f R [2,3] :

f(2)=>0 f(3)=<0, f(2)f(3) <0.

, Bolzano f [2,3],
x0 (a, ) f ( x0 ) = 0 .

: Keystone 8